Firms and wage inequality in Central and Eastern Europe - Magda, Iga; Gromadzki, Jan; Moriconi, Simone (Bonn, 2019)
"Recent studies show that firms are playing an increasingly important role in shaping wage inequality in advanced economies. We contribute to this literature by analysing wage inequality patterns and their firm dimension in Central and Eastern European countries. We use large, linked employer-employee datasets with data from the 2002-2014 period. We find that unlike in many other advanced economies, wage inequality levels have decreased in CEE countries, and particularly in those countries that previously had the highest wage inequality levels. The relative size of the between-firm component varied substantially across countries, and was largest in countries with the highest wage inequality levels. We further estimate the recentered influence function (RIF) regression and the Blinder-Oaxaca decomposition in order to investigate the micro-level determinants of wage inequality. Our findings indicate that the changes in wage inequality levels were mainly attributable to returns to workplace characteristics."